DEVELOPMENT OF A FRENCH TOURISM PROMOTIONAL VIDEO FOR TANJUNG SETIA BEACH, PESISIR BARAT, LAMPUNG - Danisa Hannaputri (Universitas Hasanuddin, 2025)
This study develops a French-language promotional video for Tanjung Setia Beach in Pesisir Barat, Lampung, known for its world-class waves attracting international surfers, including those from France. Using a limited Research and Development (R&D) approach—analysis, design, and development—the video highlights the beach's tourism appeal. Results show very good ratings: needs analysis (91.5%), content expert (88.75%), media expert (91%), and user evaluation (92%). The video effectively showcases facilities, activities, and surf events with appealing visuals and proper French use. However, it lacks information on local wisdom, an official website, testimonials, and drone footage. Minor issues include fast narration and delayed text. Despite these, the video has strong potential to attract French-speaking tourists and serve as an educational tool for tourism students.